Modeling and Analysis of Tool Wear Rate in EDM Using FEM - Kumar, Vinod (My University, 2008)
With the rapid advances in the product and process technology, newer materials are being discovered and developed. These materials have the rare combination of properties like light weight, high strength, corrosive resistance and thermal and electrical conductivity and so on. These new materials satisfy the present day product needs of Aerospace and other applications, but at the same time are more difficult to machine and manipulate. Electro Discharge Machining (EDM) is one such process which is widely employed to process these materials. EDM has been recently employed to alter the properties of the raw materials by using appropriate electrodes and various types of powders and additives in the dielectric fluid. In this thesis work the literature available in the area of MRR and TWR in EDM. It is found that the process has been successfully tried on materials like Nickel, Tungsten, Cobalt, Silicon by proper control of the parameters, electrode materials, electrolyte and powers. The objective of this work will be, modeling of a cutting tool considering the effects of the temperature and using the modified temperature concept to see the effects of temperature on the mechanical properties of the cutting tool. Once a model is developed for machining operation, it can be implemented for other processes like Die sinking and Wire cut EDM etc. An attempt is made to correlate the temperature and stress distribution patterns with the failure of the tool. The methodology will be used to develop a Finite Element Analysis program for thermal modeling to predict tool wear rate using ANSYS and also compare the results with experimental data. Considering the importance of copper for tooling applications it is chosen to investigate the TWR. Using high carbon high cromium steel as the work piece, Copper as the tool, kerosene as dielectric, experimentation was performed. At the end theoretical tool wear rate calculated using the ANSYS software is compared with the experimental results to validate the results.
M.E. (CAD/CAM and Robotics)
Keywords: EDM, Machining,FEM